Las paradojas de la subjetividad en la autoconstitución responsable de la identidad personal - Rizo-Patron de Lerner, Rosemary (2020)
The paradox of subjectivity (Crisis §§53-54) expresses not only two dissimilar methodological perspectives that stem from Modernity (the alleged objective third-person one, and the subjective first-person one), but also human beings’ essential duality as “subjects for the world” and “beings in the world”, namely, entities among entities. We explore two dimensions of the self-constitution of personal identity examined in current research, also tangible in social and political life: on one side, the reflexive, narrative, and responsible constitution of oneself and others; on the other side, the “immanent” and intersubjective intertwinement among the lived spheres of embodied emotions, desires, sensations, and their onto-phylogenetic development from instincts to reason. We highlight the silent presence of irrational (passive) motivations in (active) “rationalizations”, their impact on self-esteem and the reach of human responsibility.